Perancangan Game Digital Mobile dengan Teknik Dynamic untuk Mengubah Distorsi Kognitif Penderita Depresi Mayor pada Remaja - Amam, Muchammad Rizhamu; P, T. Arie Setiawan; Prestilliano, Jasson (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
This research investigates the potential of the digital game "Isamu" with the implementation of Dynamic Difficulty Scaling Technique as a therapeutic medium for individuals experiencing low-level major depression within the age group of 18-24 years old. With a focus on enhancing cognitive thinking, the game is designed to contribute positively to the development of adaptive and positive thinking patterns in players. The research findings indicate that the use of Dynamic Difficulty Scaling Technique yields positive outcomes as expected, with challenges tailored to individual abilities. This study not only supports the use of games as a therapy tool for major depression but also demonstrates further potential development in this field.